An eclamptic dilemma: a rare case of old cerebral venous thrombosis with antepartum eclampsia - Madhurya Nagesh,; Gowda, Nandini Srinivasa; Thonangi, Aashritha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Pregnancy and puerperium are associated with an increased risk of venous thromboembolic events, including cerebral venous thrombosis (CVT), which accounts for a significant proportion of pregnancy-related strokes. Women with a previous history of CVT are at increased risk of recurrence and hypertensive disorders of pregnancy. We report a rare case of a primigravida presenting with antepartum eclampsia and recurrent seizures, later diagnosed as posterior reversible encephalopathy syndrome with radiological evidence of old CVT. The patient had discontinued prior anticoagulation and antiepileptic therapy and did not disclose her medical history during antenatal care. Prompt multidisciplinary management led to a favorable maternal outcome. This case highlights the diagnostic challenge of differentiating eclampsia from neurological sequelae of previous CVT and underscores the importance of detailed history-taking and thromboprophylaxis in high-risk pregnancies.